2022 International Conference on Information Networking (ICOIN) 2022
DOI: 10.1109/icoin53446.2022.9687159
|View full text |Cite
|
Sign up to set email alerts
|

Capacity Limitation of Small Cell Densification

Abstract: Deployment of small cells is considered as an easy approach for adding capacity to the system. However, it is important to realize that in a non-noise limited system, each additional cell increases the interference in the system. The target of this paper is to show the capacity limitation of the cellular network with an increasing number of small cells in a network. Ultra-dense deployment of small cells implies a high probability of line of sight (LOS) transmission between the transmitter (TX) and receiver (RX… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…It should be noted that at high frequencies and in the LOS environment, the strength of diffracted paths has lower signal strength compared with LOS and reflected paths. In an LOS environment with cells utilizing the same frequency and polarization, the LOS path is the major contributor to interference between them, as presented in [3]. In the case of utilizing orthogonal polarization in immediate neighbor cells, the interference distance is three times (39) longer for the base station utilizing omnidirectional directional antenna, as shown in Fig.…”
Section: Polarizationmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that at high frequencies and in the LOS environment, the strength of diffracted paths has lower signal strength compared with LOS and reflected paths. In an LOS environment with cells utilizing the same frequency and polarization, the LOS path is the major contributor to interference between them, as presented in [3]. In the case of utilizing orthogonal polarization in immediate neighbor cells, the interference distance is three times (39) longer for the base station utilizing omnidirectional directional antenna, as shown in Fig.…”
Section: Polarizationmentioning
confidence: 99%
“…Continuously increasing capacity requirements and higher frequencies of new technologies lead to dense base station site grids and small cells. In reference [3], it is shown that the system performance of densely implemented small cell infrastructure is squeezed as a function of site/cell distance. It is observed that the bad SIR area in between neighbor cells inversely increases as a function of site distance when the same frequency and polarization are used in neighbor cells.…”
Section: Introductionmentioning
confidence: 99%